A Said dictionary - Radhakrishnan, R. (Rajagopalan) (Hoboken, N.J. : John Wiley & Sons Inc., 2012)
This interpretive dictionary introduces the critical and theoretical world of distinguished literary and cultural critic Edward W. Said through the crucial terms and concepts central to his work. Compares and contrasts Said's perspective with other key theorists, such as Derrida, Spivak, Foucault, and JamesonDescribes the crucial terms and concepts central to Said's workPlaces the development of Said's work within its historical context.
Introduction -- Affiliation -- Auerbach, Eric -- Beginnings: -- Between/betweenness -- Centrism -- Conrad, Joseph -- Contrapuntal criticism: Culture and imperialism -- Democratic criticism -- Exile -- Humanism -- Intellectual, the -- Linguicity -- Narrative -- Nationalism -- Oppositional criticism or consciousness -- Orient/oriental/orientalism -- Philology -- Postcoloniality -- Professionalism -- Representation -- Secular criticism -- Speaking truth to power -- Specular/border intellectual -- Style -- Text/textuality -- Theory -- Traveling theory -- Vico, Giambattista -- Virtuosity -- Voyage in, The -- Worldliness -- Zionism.
Includes bibliographical references and index.
Print version record.
Keywords: Said, Edward W. -- Criticism and interpretation; Said, Edward W. -- Language -- Glossaries, etc; Said, Edward W; Said, Edward W; LITERARY CRITICISM -- Semiotics & Theory; Language and languages; Electronic books; Criticism, interpretation, etc; Glossaries, vocabularies, etc